Targeting advanced glycation end products: potential therapeutic approaches for mitigating diabetic intervertebral disc degeneration? - Wang, Luyang; Shao, Qipeng; Wu, Haiyang; Li, Cheng (Frontiers in Endocrinology, 2025)
Diabetes mellitus is strongly associated with accelerated intervertebral disc degeneration, a condition that significantly contributes to lower back pain and reduced quality of life. Emerging evidence indicates that advanced glycation end products (AGEs) are key mediators in the pathophysiology of disc degeneration through the stimulation of inflammatory pathways, promotion of oxidative stress, and induction of extracellular matrix modifications. This review critically examines current literature on the role of AGEs in diabetic disc degeneration and evaluates potential therapeutic interventions aimed at mitigating these deleterious effects. Targeting AGEs represents a promising therapeutic avenue to mitigate diabetic intervertebral disc degeneration. The current evidence supports the rationale for further investigation into AGE inhibitors, cross-link breakers, and receptor for AGEs modulators as potential treatment strategies. However, to translate these findings into clinical practice, well-designed clinical trials are required to validate the efficacy and safety of these interventions, as well as to optimize treatment protocols.